Determination of Lead and Cadmium level in cattle offals, water and feed in Omdurman locality –Sudan - Sahar Mohammedan Joda; Hind Abdelaziz Elnasri (International Journal on Food, Agriculture and Natural Resources, 2023)
This study was carried out to determine the level of Cadmiuum (Cd) and Lead (Pb)  in cattle meat, offals, water and feed samples. The samples were obtained from Al Muwalih area (Omdurman locality- Sudan). Laboratory analysis was carried out using Atomic Absorption Spectroscopy. Usually, animals are transported from theWestern region of Sudan to the capital city Khartoum, were after few months will be slaughtered for consumption. The highest concentration of Cd and Pb was observed in kidney and liver with a mean of 0.0302 ±0.003mg/g and 0.259± 0.008mg/g respectively. High levels of Cd and Pb were also detected in water and feed samples. It is thus important to supply safe feed for animals to safeguard animal health and reduce the risk of exposure of consumers to heavy metals.